2019
DOI: 10.1101/607325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neglected part of the microbiome: Prophage TJ1 regulates the bacterial community of the metaorganism Hydra

Abstract: Many multicellular organisms are closely associated with a specific bacterial community and therefore considered "metaorganisms". Controlling the bacterial community composition is essential for the stability and function of metaorganisms, but the factors contributing to the maintenance of host specific bacterial colonization are poorly understood. Here we demonstrate that in Hydra the most dominant bacterial colonizer Curvibacter sp. is associated with an intact prophage which can be induced by different envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Genome analyses indeed proved the presence of an integrated and inducible prophage in the genome of Curvibacter . The isolated phage of Curvibacter is able to infect other bacteria of Hydra's microbiome, like Duganella, and influences their abundances in culture and during Hydra colonization (Lange et al 2019). These results highlight the importance of an intact microbiome for Hydra's health, and Curvibacter's role as an essential part of a protective and homeostatic microbiome.…”
Section: Curvibacter Function In the Hydra Metaorganismmentioning
confidence: 81%
“…Genome analyses indeed proved the presence of an integrated and inducible prophage in the genome of Curvibacter . The isolated phage of Curvibacter is able to infect other bacteria of Hydra's microbiome, like Duganella, and influences their abundances in culture and during Hydra colonization (Lange et al 2019). These results highlight the importance of an intact microbiome for Hydra's health, and Curvibacter's role as an essential part of a protective and homeostatic microbiome.…”
Section: Curvibacter Function In the Hydra Metaorganismmentioning
confidence: 81%
“…Although viral therapies do show considerable promise they do have their drawbacks (Loc-Carrillo and Abedon, 2011;Zheng M. et al, 2019). In the case of bacteriophage therapy, although some studies have shown that the introduction of bacteriophages can have only minimal or transient effects on non-target bacterial populations (Reyes et al, 2013;Nale et al, 2018), other studies have shown that the impact could be broader (Hsu et al, 2019;Lange et al, 2019). There is also the issue of bacterial resistance development, and although currently this is mainly overcome by the use of bacteriophage "cocktails" (mixes containing multiple distinct bacteriophages; Nale et al (2016)), resistance can still occur, meaning co-use with antibiotics can be required to completely eliminate the target organism (Oechslin et al, 2016).…”
Section: Viruses In Colorectal Cancer Treatmentmentioning
confidence: 99%